Leadership DynamicsHollanderEdwin P. Leadership Dynamics (New York: The Free Press, 1978), 212 pp., $12.95. - Johnson, Dewey E. (Academy of Management Review, 1979)
This article presents a review of the book ?Leadership Dynamics,? by Edwin P. Hollander.